THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, ORGANIZATIONAL CULTURE, AND JOB SATISFACTION ON THE ORGANIZATIONAL COMMITMENT OF VOCATIONAL HIGH SCHOOL TEACHERS IN PALANGKA RAYA CITY - Valery Yulie; Aslamiah Aslamiah; Ahmad Suriansyah (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
The advancement of education in the Industrial Revolution 4.0 era requires strengthening human resource quality, particularly teachers as central actors in the learning process. The relatively low job satisfaction among state vocational high school teachers in Palangka Raya City has implications for their motivation and organizational commitment. This study examines the effects of transformational leadership, organizational culture, and job satisfaction on teachers' organizational commitment, including the indirect effects mediated by job satisfaction. A quantitative survey design was employed involving 157 teachers selected through proportional random sampling from public vocational high schools in Palangka Raya. Data were collected using a validated and reliable Likert-scale questionnaire. Path analysis was applied to assess causal relationships and to estimate both direct and indirect effects among the studied variables. The results indicate that all variables were categorized as high. Transformational leadership (0.382), organizational culture (0.289), and job satisfaction (0.227) exhibited significant direct effects on organizational commitment. In addition, transformational leadership (0.544) and organizational culture (0.215) demonstrated direct effects on job satisfaction. Indirect effects were also observed, with transformational leadership (0.186) and organizational culture (0.082) influencing organizational commitment through job satisfaction.These findings confirm that transformational leadership, organizational culture, and job satisfaction are key determinants of teachers' organizational commitment. Strengthening transformational leadership practices, fostering a supportive organizational culture, and enhancing job satisfaction are recommended to optimize teachers' organizational commitment.